What workforce preparation is required for successful implementation of nurse prescribing under supervision?. Issue 2 (April 2023) - Fox, Amanda; Thamm, Carla; Crawford-Williams, Fiona; Joseph, Ria; Cardiff, Lynda; Thoms, Debra; Nissen, Lisa; Yates, Patsy; Chan, Raymond Javan
ABSTRACT: Background: Nurse prescribing is proposed globally in a variety of models in an attempt to meet health needs of the growing population. Providing appropriate preparation, knowledge, and supported skill development commensurate with this expanded scope has been identified as a key component to the successful adoption of this practice change. Aim: To explore nurses' preferences for the educational preparation and support required to maximise uptake of expanding nursing practice to include prescribing according to a supervised model. Methods: A cross-sectional online survey, tested for face and content validity, was distributed to registered general nurses across Australia excluding nurse practitioners, enrolled nurses, and student nurses between March and July 2021. Quantitative data relating to demographics, nursing experience, and educational requirements to become a prescriber were analysed descriptively. Pearson χ 2 tests were used to examine associations between participant demographics and preferences for education. Binary logistic regression was used to further examine whether demographic factors were significant predictors of educational preferences. Open-ended responses were analysed using content analysis techniques. Findings: There were 4, 424 surveys completed by nurses from all jurisdictions. More than half of (n=2, 907, 65.7%) respondents considered that education should be delivered by health services in conjunction with universities using a blended approach with workplace integrated practice. Respondent's desire authorised prescriber support and a multidisciplinary approach for successful adoption. The most frequently reported (n=3, 523, 79.6%) factor influencing the desire to undertake a specific program was course accreditation at a national level and contribution to a formal qualification. χ 2 tests showed significant associations between participants characteristics and educational preparation factors; however, logistic regression showed a similar trend for all educational preparation items with no significant effect of age group, qualification, years of experience or state groups. Discussion: Implementation of an expanded scope of practice to include prescribing under the supervision of an authorised prescriber requires a nursing workforce prepared to undertake further education and authorised prescriber's support. Nurses seek a rigorous national educational program delivered in collaboration with colleagues. Conclusion: Health services planning to expand nursing practice to include prescribing should consider issues raised in this study. The findings highlight areas for future research and actions to optimise uptake of this new nursing role.